Exercise recommendations and referral patterns of oncology professionals. Issue 3 (29th June 2021) - Mizrahi, David; Murnane, Andrew; Quinn, Sharni; Crowe, Jessica; Rosenbaum, Simon; Adams, Diana; Atkinson, Morgan
Abstract: Background: Exercise physiologists and physiotherapists can provide exercise interventions for cancer survivors; however, many do not access this support. Our primary aim explored referral habits to exercise professionals and attitudes of oncology professionals. Secondary aims explored fitness levels of oncology professionals and the relationship between fitness and exercise referral habits. Methods: Oncology professionals ( n = 67) attending a national cancer conference in Australia participated in this cross‐sectional study (23% doctors, 11% nurses, 25% allied health, and 41% other). A subgroup ( n = 49) completed a fitness assessment measuring aerobic fitness (3‐minute step test), muscle strength (handgrip dynamometry), and body composition (waist‐to‐hip ratio). Oncology professionals in a position to refer patients to exercise professionals were assessed on their history of patient referrals. Results: Sixty‐seven of 750 eligible conference delegates participated (9% recruitment rate), of which 73% completed fitness assessments. Participants displayed above average physical activity and fitness levels with 60% meeting exercise guidelines. The majority (92%) agreed that exercise is important among cancer survivors to attenuate treatment‐associated symptoms. Most understand the role of exercise physiologists (61%) and physiotherapists (64%) in cancer care. Seventy‐three percent reported that referral to exercise professionals is optimal to increase exercise participation. Most (82%) oncology professionals who are able to refer patients to exercise professionals have self‐reported doing so, while 91% recommended exercise themselves. Sixty‐two percent were aware of evidence‐based exercise guidelines. Fitness levels ( p = 0.25), strength ( p = 0.88), and physical activity ( p = 0.33) did not impact referrals made to exercise professionals. Conclusion: There was high awareness exercise‐oncology benefits and evidence‐based guidelines existed among sampled participants. Oncology professionals understand the role of exercise professionals, reflected by high self‐reported referral rates. Implementing referral pathways to exercise professionals in cancer care may facilitate improved patient outcomes. Abstract : Most oncology professionals are aware of exercise guidelines and understand the role that exercise professionals have in cancer care. While referral rates to exercise professionals were high on our study, there was no relationship between physical fitness levels of oncology professionals and their referral rates to exercise professionals.